Effects of electric field on interfacial microstructure and shear strength of diffusion bonded α-Al2O3/Ti joints. Issue 1 (January 2015) - Pan, Rui; Wang, Qing; Sun, Dongli; He, Peng
Abstract There have been reports about electric-field-assisted diffusion bonding of electrolyte materials, but how dielectric materials behave in such process hasn't been seen in literature. In this work, a dielectric ceramic of α-Al2O3 was successfully diffusion bonded to pure Ti under electric field with improved diffusion of elements and mechanical properties of the joints. Mechanism of the promoting effects of electric field was revealed. By turning-direction polarization of α-Al2O3 molecules and electrostatic attraction force between Ti4+ ions and electronegative O atoms, the diffusion of elements at the interface is promoted, thus resulting in thicker reaction layers and higher shear strengths, which reach the maximum of 110.1 MPa under 1100 V voltage, 50.2% higher than that without electric field treatment. Electric-field-assisted diffusion bonding may be a promising method to improve joint strength and lower undesirable bonding parameters.